The impact of Covid-19 on the behavior of actors and the regulation of the Moroccan stock market - Hnaka, Hadbaa; Ouassou, Fatima Ezzahra; Riad, Lamyaa (Annals of Management and Organization Research, 2023)
Purpose: This study examines the impact of the COVID-19 health crisis on the behavior of actors and legislation on the Moroccan stock market. Research Methodology: This study uses the collection and exploitation of data from key institutional reports and legal data limited to certain laws and regulations (excluding relevant case law and doctrine) attesting to the orientations of capital market authorities following the declaration of a state of health emergency. Results: The analysis revealed that the measures taken by the government, central bank, and AMMC helped curb the capital market and provide investors with the tools they need to strengthen the resilience of Morocco's capital market. Limitations: The first concerns the difficulty of analyzing the long-term effects of a health crisis. The second limitation concerns the existing models, theories, and methodological limitations. Contribution: This documentary study synthesizes the psychic reactions and behaviors of Moroccan stock exchange market actors in times of crisis. In addition, it enables researchers to better understand the legal interventions taken to regulate and redirect behaviors influenced by the pandemic in the Moroccan capital market.